(untitled) (Medical Forum Monthly, 2024)
Objective: To measure the frequency of obesity in male and female medical students of Multan Medical and Dental College using BMI for quantification of Obesity. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Multan Medical and Dental College, Multan in March, 2017 Materials and Methods: A total of 100 medical students from all five years, 50 males and 50 females of ages 18-25 were included in the study. A questionnaire was filled out by subjects asking them about their age, gender, weight in kilograms and height in meters. Results: Students were classified into different categories of obesity according to their BMI with reference to world health organization (WHO) criteria. Out of 100 students, 68% fell into the normal range of BMI, 23% were overweight and 7% fell into Obese Class 1. Out of 50 male students, 33% had normal BMI, 26% were overweight and 8% fell in obesity class 1. Out of 50 female students, 35% had normal body mass index (BMI) 20% were overweight and 6% fell in Obesity Class 1. Conclusion: This study suggests that obesity and overweight are prevalent among both male and female medical students. There is an increasing need to carry out more studies, preferably with larger sample size, to assess the burden and impact of this problem.